Effect of integrated nutrient management on baby corn–rice cropping system: economic yield, system productivity, nutrient-use efficiency andsoil nutrient balance - SHARMA, R C; BANIK, P (The Indian Journal of Agricultural Sciences, 2012)
The study was conducted to estimate the nutrient-use efficiency and soil nutrient balance of integrated nutrient management, five combinations of organic and inorganic sources of nutrients. Both partial factor productivity and agronomic- use efficiency of nitrogen, phosphorus and potassium was recorded maximum in F3 (70% RD of NPK through inorganic fertilizers + 30% N through FYM), F2 (70% RD of NPK through inorganic fertilizers + 30% N through vermicompost) and F1 (recommended dose (RD) of NPK (150:26:33) through fertilizers), respectively. Apparently recovery efficiency for N and K was highest in F1, whereas P in F3. Physiological-use efficiency (PFP) was highest in F3, followed by F1 and F2 treatment. INM showed actual N gain but apparent N losses. Maximum actual N gain was recorded where nutrients were applied through equal proportion (50:50) of organic and inorganic sources. Similar trend was recorded for actual and apparent P loss/gain as recorded for N. Results showed losses in actual K but gain in apparent K for all the treatments.